Does high body mass index increase the risk of shoulder instability surgery? The LUXE prospective cohort study on 227 recurrent anterior shoulder instability - Vincent Roy, MD, MSc; Claire Bastard, MD, MSc; Emilie Sandman, MD, MSc, FRCSC; Alexis Rousseau-Saine, MD, FRCSC; Marie-Lyne Nault, MD, PhD, FRCSC; Dominique M. Rouleau, MD, MSc, FRCSC (JSES International)
Background: The aim of this study was to determine whether body mass index (BMI) plays a role in overall morbidity following shoulder instability surgery and whether some surgical techniques are BMI-sensitive. Methods: A prospective, multicenter database was created that included the following three surgical techniques: arthroscopic Bankart (AB), arthroscopic Bankart with remplissage (ABR), and Open Latarjet (OL). Patient data (demographic, strength, laxity and functional outcomes (Disability of the Arm, Shoulder, and Hand [QuickDASH]; Western Ontario Shoulder Instability Index; and QuickDASH Pain subscore) were compared at enrollment and last postoperative follow-up. Functional outcomes, complications, and postoperative outcomes were compared between the different groups and then subdivided by BMI. Follow-up radiographs were evaluated for graft position and complications for all patients who underwent OL. Results: A total of 227 patients (164 men, 63 women) were included with at least 1-year follow-up (3.3y AB (n = 126), 4.5y ABR (n = 34), and 3y OL (n = 62)). At baseline, patients with high BMI (37(17%)) had significantly worse QuickDASH Pain subscores (2.9 ± 1.0, P value <.05) and QuickDASH (46.8 ± 21.6, P value < .001) scores compared to all other BMI groups. All BMI groups had similar QuickDASH (P value .22) and Western Ontario Shoulder Instability Index (P value .69) scores at last follow-up. Complication rates for patients with high BMI were significantly higher in ABR compared to AB (P value .042) and so were reoperation rates in patients with high BMI after OL compared to patients with high BMI after ABR (9.5%, P value .049). Conclusion: Patients with high BMI showed significantly worse baseline functional scores but no difference was found in postoperative functional scores between BMI groups. Complication rates were significantly higher in patients with high BMI following ABR compared to AB, and so were reoperation rates in patients with high BMI undergoing Latarjet compared to AB.